Diagnostic accuracy of hyperbilirubinaemia in anticipating appendicitis and its severity. Issue 9 (4th December 2014) - Muller, Sven; Falch, Claudius; Axt, Steffen; Wilhelm, Peter; Hein, Dirk; Königsrainer, Alfred; Kirschniak, Andreas
Abstract : Background: Hyperbilirubinaemia is reported to be a positive predictor in diagnosing appendicitis and especially appendiceal perforation. We, therefore, analysed the diagnostic accuracy of serum bilirubin in anticipating appendicitis and its severity. Methods: All consecutive patients undergoing appendectomy for suspected appendicitis from May 2009 to August 2011 were analysed. Patients were classified based on final histopathological findings into the groups: no appendiceal inflammation, non-perforated appendicitis and perforated appendicitis. Primary outcome was the diagnostic accuracy of serum bilirubin levels in discriminating between no appendiceal inflammation and any appendicitis (perforated and non-perforated appendicitis) and non-perforated and perforated appendicitis. Results: Of 493 analysed patients, 125 (25%) had no appendiceal inflammation, 312 (64%) had non-perforated appendicitis and 56 (11%) had perforated appendicitis. The proportion of patients with bilirubin elevation (>1.1 mg/dL) was different between those with no appendiceal inflammation (14%) and any appendicitis (36%) (p<0.0001), and between non-perforated appendicitis and perforated appendicitis 48% (p=0.04). However, the positive and negative likelihood ratios (LRs) for an elevated bilirubin were poor at discriminating the groups: no appendiceal inflammation versus any appendicitis (LR+ 2.62 (95% CI 1.65 to 4.16) and LR− 0.75 (95% CI 0.67 to 0.83)) and non-perforated appendicitis versus perforated appendicitis (LR+ estimate 1.74 (95% CI 1.28 to 2.38) and LR− 0.72 (95% CI 0.55 to 0.93)). Conclusions: Hyperbilirubinaemia is present in acute appendicitis but has a low diagnostic accuracy in discriminating between any appendicitis versus no appendiceal inflammation and perforated versus non-perforated appendicitis and is, therefore, of limited value in clinical routine. Trial registration number: NCT01698099.